Keputusan Pembelian Kosumen Secara Online: Peran Presepsi Risiko dan Manfaat - Hanan Maulana; Erlinda Sholihah; Risma Nurhapsari (CV. ITTC INDONESIA, 2025)
This research is motivated by changes in consumer shopping behavior during the Covid-19 pandemic, which led to an increase in online transactions, particularly for electronic products. The purpose of this study is to examine the influence of perceived risk and perceived benefit on consumers’ online purchasing decisions at Candi Elektronik Store in Surakarta. A quantitative approach was employed, with data collected through questionnaires distributed to 190 respondents, and analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the SmartPLS software. The findings show that perceived risk has a positive and significant effect on purchasing decisions, meaning that the lower the perceived risk, the greater the likelihood of consumers making a purchase, while perceived benefit also has a positive and significant effect, indicating that the higher the perceived benefit, the stronger consumers’ tendency to engage in online transactions. The R-Square value of 0.279 indicates that the two independent variables explain 27.9% of the variance in purchasing decisions, while the remaining 72.1% is influenced by other factors beyond this study.